Adverse Cardiovascular Response to Aerobic Exercise Training: Is This a Concern? - Leifer, Eric S; Mikus, Catherine R; Karavirta, Laura; Resnick, Benjamin D; Kraus, William E; Häkkinen, Keijo; Earnest, Conrad P; Fleg, Jerome L (Medicine and science in sports and exercise, 2016)
Aerobic exercise training in sedentary individuals improves physical fitness and various cardiovascular (CV) biomarkers. Nevertheless, there has been controversy as to whether exercise training may adversely affect some biomarkers in a small segment of the population. The purpose of this study was to investigate whether clinically significant worsening of CV biomarkers was more prevalent among individuals randomized to a supervised endurance training program as compared with those randomized to a control condition. Baseline and end of study measurements of fasting insulin (FI), triglycerides (TG), resting systolic blood pressure (SBP), and HDL cholesterol (HDL-C) were obtained on 1188 healthy sedentary subjects from 4 clinical studies. Each study randomized subjects to 4- to 6-month supervised aerobic exercise programs or to a control group of no supervised exercise training. For each of the 4 CV biomarkers, we calculated the respective proportions of control and exercise group subjects whose baseline-to-follow-up changes were greater than or equal to previously reported adverse change (AC) thresholds. Those thresholds were increases of 24 pmol · L(-1) or greater for FI, 0.42 mmol · L(-1) or greater for TG, 10 mm Hg or greater for SBP, and a decrease of 0.12 mmol · L(-1) or greater for HDL-C. The respective proportions of subjects meeting the AC threshold in the control and exercise groups were 15.2% versus 9.6% (P = 0.02) for FI, 14.9% versus 13.1% (P = 0.37) for TG, 16.9% versus 15.8% (P = 0.52) for SBP, and 28.6% versus 22.5% (P = 0.03) for HDL-C. All were nonsignificant at the 0.0125 Bonferroni threshold adjusting for multiple comparisons. These findings do not support the concept that aerobic exercise training increases the risk of adverse changes in the CV biomarkers we studied.